Right on social protection in the context of social state - Нижник, Н. Р.; Гуменюк, І. О. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article exposes the content of the right to social protection, the necessity of its legislative update.